Treadmill Training with HAL Exoskeleton—A Novel Approach for Symptomatic Therapy in Patients with Limb-Girdle Muscular Dystrophy—Preliminary Study - Sczesny-Kaiser, Matthias; Kowalewski, Rebecca; Schildhauer, Thomas A.; Aach, Mirko; Jansen, Oliver; Grasmücke, Dennis; Güttsches, Anne-Katrin; Vorgerd, Matthias; Tegenthoff, Martin (Frontiers in Neuroscience, 2017)
Purpose: Exoskeletons have been developed for rehabilitation of patients with walking impairment due to neurological disorders. Recent studies have shown that the voluntary-driven exoskeleton HAL® (hybrid assistive limb) can improve walking functions in spinal cord injury and stroke. The aim of this study was to assess safety and effects on walking function of HAL® supported treadmill therapy in patients with limb-girdle muscular dystrophy (LGMD). Materials and methods: Three LGMD patients received 8 weeks of treadmill training with HAL® 3 times a week. Outcome parameters were 10-meter walk test (10MWT), 6-minute walk test and timed-up-and-go test (TUG). Parameters were assessed pre and post training and 6 weeks later (follow-up). Results: All patients completed the therapy without adverse reactions and reported about improvement in endurance. Improvements in outcome parameters after 8 weeks could be demonstrated. Persisting effects were observed after 6 weeks for the 10MWT and TUG test (follow-up). Conclusions: HAL® treadmill training in LGMD patients can be performed safely and enables an intensive highly repetitive locomotor training. All patients benefitted from this innovative method. Upcoming controlled studies with larger cohorts should prove its effects in different types of LGMD and other myopathies.